1998
DOI: 10.1148/radiology.208.1.9646792
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR imaging evaluation of chondropathy in osteoarthritic knees.

Abstract: Quantification of chondropathy with MR imaging is feasible and well correlated with anatomic cartilage breakdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 0 publications
3
71
0
1
Order By: Relevance
“…The discrepancy between MRI and arthroscopy seen with grade 1 lesions can be attributed to the fact that lesions without surface irregularities are inherently difficult to diagnose arthroscopically and, in fact, the authors of such studies have found that MRI can "overgrade" intracartilaginous lesions relative to arthroscopy (26). Furthermore, those investigators concede that the arthroscopic correlate to an MRI grade 1 lesion, which is referred to as cartilage softening or swelling, can be appreciated only by gentle palpation of the articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between MRI and arthroscopy seen with grade 1 lesions can be attributed to the fact that lesions without surface irregularities are inherently difficult to diagnose arthroscopically and, in fact, the authors of such studies have found that MRI can "overgrade" intracartilaginous lesions relative to arthroscopy (26). Furthermore, those investigators concede that the arthroscopic correlate to an MRI grade 1 lesion, which is referred to as cartilage softening or swelling, can be appreciated only by gentle palpation of the articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…The cartilage defects were graded on the MR images with a modification of a previous classification system (10)(11)(12) at medial tibial, medial femoral, lateral tibial, and lateral femoral sites as follows: grade 0 ϭ normal cartilage; grade 1 ϭ focal blistering and intracartilaginous low-signal intensity area with an intact surface and bottom; grade 2 ϭ irregularities on the surface or bottom and loss of thickness of Ͻ50%; grade 3 ϭ deep ulceration with loss of thickness of Ͼ50%; grade 4 ϭ full-thickness cartilage wear with exposure of subchondral bone ( Figure 1). We found that the cartilage surface in some images was still regular but that cartilage adjacent to subchondral bone became irregular, so we included this in the classification system.…”
Section: Methodsmentioning
confidence: 99%
“…Medication regimens and any changes in them were closely monitored and recorded. The use of indomethacin was not permitted because of its potential to promote degeneration of OA cartilage (13,(51)(52)(53). Likewise, the use of glucosamine sulfate was not permitted because of its potential to affect OA progression (54).…”
Section: Methodsmentioning
confidence: 99%
“…The validity of measurements of JSW in knee OA has been demonstrated by correlations between the medial tibiofemoral JSW and the sum of the thickness of both the femoral and the tibial articular cartilage (11). The use of arthroscopy to assess cartilage appears to be reliable and sensitive to change at 1 year (12,13). However, only the cartilage surface can be evaluated, and the method is both semiquantitative and, most importantly, invasive, which is problematic for multicenter studies.…”
mentioning
confidence: 99%